2018
DOI: 10.1177/1461444818793421
|View full text |Cite
|
Sign up to set email alerts
|

Stumbling upon the other side: Incidental learning of counter-attitudinal political information on Facebook

Abstract: Drawing on a panel survey and a laboratory experiment, this study investigates incidental exposure to counter-attitudinal political information on Facebook. The frequency of Facebook use is found positively associated with incidental exposure to counter-attitudinal political information, suggesting the important role of Facebook in exposing users to political disagreement. In addition, the findings of the experiment indicate that individuals coming across counter-attitudinal Facebook posts are able to recogniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 62 publications
1
47
1
Order By: Relevance
“…This makes them more likely to affiliate with like-minded others and create homogeneous groups. While social media users may commonly be fully in control of their virtual acquaintances (e.g., in terms of friending or following someone or a news channel), they may not have full control over the information and stances they are exposed to incidentally, for instance, when browsing through certain Facebook or YouTube news channels (Lu & Lee, 2018). Following this logic, it seems worthwhile to ask to what extent users are actually exposed to and in contact with opinions they disagree with.…”
Section: Background Political Homogeneity In Online Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…This makes them more likely to affiliate with like-minded others and create homogeneous groups. While social media users may commonly be fully in control of their virtual acquaintances (e.g., in terms of friending or following someone or a news channel), they may not have full control over the information and stances they are exposed to incidentally, for instance, when browsing through certain Facebook or YouTube news channels (Lu & Lee, 2018). Following this logic, it seems worthwhile to ask to what extent users are actually exposed to and in contact with opinions they disagree with.…”
Section: Background Political Homogeneity In Online Communicationmentioning
confidence: 99%
“…Empirical research addressing the potential existence of echo chambers in online networks has been based on two different approaches: On the one hand, survey research has relied on subjective estimates by social media users. This line of research, asking participants how frequently they are exposed to opinion or ideological diversity, has shown that on social media, people are incidentally exposed to heterogeneous opinions (e.g., Kim, 2018;Lee, Choi, Kim, & Kim, 2014;Lu & Lee, 2018;Vaccari et al, 2016). On the other hand, another series of studies used observational data and made use of computational methods, especially focusing on SNAs.…”
Section: Background Political Homogeneity In Online Communicationmentioning
confidence: 99%
“…Moreover, our findings provide some support for the existence of a selfreinforcing mechanism (see Slater, 2007) between congruent SNS environments and opinion strength (indicated by the marginal correlation between opinion strength and selective exposure). However, given the possibility of incidental exposure to incongruent opinions via SNS (Lu & Lee, 2018), the degree of political congruence that users are exposed to in these environments may not be sufficient for such dynamics to unfold (O'Hara & Stevens, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Opinions and opinion climates vary in the degree of congruence and a congruent opinion climate can thus be conceived of as one that is in line with or similar to the opinion of an individual. Besides addressing antecedents of individuals' exposure to congruent (e.g., Wojcieszak & Garrett, 2018) and incongruent opinion climates (e.g., Lu & Lee, 2018), a number of studies dealt with the cognitive consequences of being exposed to congruent and incongruent views and in particular with the question of how the exposure to congruent and incongruent information affects political attitudes (e.g., Huckfeldt et al, 2004;Stroud, 2010).…”
Section: Cognitive Effects Of Congruence and Incongruence: Opinion Stmentioning
confidence: 99%
“…Prior research examining the use of Facebook in political campaigns established that Facebook users encounter news online mostly by chance while they are using the Internet for other things (Boyd & Ellison, 2008;Ellison, Steinfield & Lampe, 2007;Lu, & Lee, 2019;Matsa & Lu, 2016). Past research has assumed that Facebook users believe that their Facebook friends are interested in their lives and activities as well as their problems (Brailovskaia, Rohmann, Bierhoff, Schillack & Margraf, 2019).…”
Section: Facebook Communication and Marketing Influence On Decision-mmentioning
confidence: 99%